DAMPAK IBU BEKERJA TERHADAP PERKEMBANGAN SOSIAL ANAK USIA DINI DI RA AR-RAHMAH PRAGAAN SUMENEP (VYGOTSKY) - Ulfah (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This study aims to analyze the impact of the presence of working mothers on children's social development using Vygotsky's theoretical perspective as an analytical framework. The method used is descriptive qualitative research, which relies on in-depth analysis of phenomena that occur in society, especially related to children's social interactions in the context of working mothers. The results of the study indicate that even though mothers work, children can still experience positive social development if there is sufficient interaction with other family members and the school environment. The role of grandmothers or other close family members in caring for children has also proven effective in maintaining a balance between work and family responsibilities. In addition, the results of this study highlight the importance of cooperative learning and scaffolding in supporting child development, as well as the role of teachers in providing a learning environment that is in accordance with Vygotsky's theory. The implications of this study indicate that the balance between work and family life, as well as adequate emotional support, are important factors in supporting children's holistic development. The emotional impacts arising from the presence or absence of working mothers must also be considered in designing policies that support family welfare and child development. Keywords: Children's education; the role of working mothers; social interaction